Impact of Augmented Reality on Generation Z’s Purchasing Intention: Behavior Analysis in a Digital Environment - Gil Ibáñez, Marta; Sans Serrano, Alexandra; Lavandeira Menedo, Yago; LLorens Plana, Monserrat (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
Augmented reality, as a tool in digital marketing, enhances the shopping experience. This research examines how augmented reality influences the behaviour and purchase intention of Generation Z in e-commerce. An augmented reality tool was developed for the online purchase of glasses, evaluating its impact on 105 young users. The study employed a quantitative, descriptive, and cross-sectional method. The results reveal that, although there is interest in using these tools, young users do not significantly increase their purchase intention for a product through their use.